A rare case of Haemophilus parahaemolyticus pneumonia - Devaraj, Navin Kumar; Amin Nordin, Syafinaz (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Pneumonia is a common lung infection. Common bacterial cause of this serious lung infection includes Streptococcus pneumoniae, Haemophilus influenzae and Mycoplasma pneumoniae. Haemophilus parahaemolyticus pneumonia is an uncommon cause of bacterial pneumonia, occurring mainly as an opportunistic pathogen in immunocompromised patients as in this case, diabetes mellitus. Therefore, this case report will look at a case of 49-year-old man who was diagnosed with this uncommon pathogen which was successfully eradicated with antibiotics. This case report will look at a case of 49 years old who was diagnosed with this uncommon pathogen which was successfully eradicated with antibiotics.